Chemoradiotherapy for anal cancer: clinical trials past, present and future. (June 2014) - Cooper, Rachel; Casanova, Nathalie; Sebag-Montefiore, David
SUMMARY: Anal cancer is a rare cancer whose incidence is increasing in the UK. It is associated with human papilloma virus infection and smoking and is more common in women and immunosuppressed individuals, including those with transplants and HIV infection. The current standard of care is chemoradiotherapy (CRT) to the pelvis with surgery reserved for patients where CRT is contraindicated or as salvage treatment for residual disease or recurrence post-CRT. Radiotherapy combined with mitomycin-C and 5-fluorouracil has emerged as the standard of care following a series of six well-conducted Phase III trials. Trials have shown no benefit for cisplatin-based combination regimens either concurrently, adjuvantly or neoadjuvantly.